A converse duality theorem on higher-order dual models in nondifferentiable mathematical programming - Yang, X.; Teo, Kok Lay (Springer Verlag, 2010)
We consider in this paper Mond–Weir type higher-order dual models in nondifferentiable mathematical programming introduced by Mishra and Rueda (2002, J. Math. Anal. Appl. 272, 496–506). We give a converse duality theorem on Mond-Weir type higher-order dual model under mild assumptions.